Synergistic growth inhibitory effects of Phyllanthus emblica and Terminalia bellerica extracts with conventional cytotoxic agents: Doxorubicin and cisplatin against human hepatocellular carcinoma and lung cancer cells - Khosit Pinmai (2018)
Aim: To examine the growth inhibitory effects of Phyllanthus emblica (P. emblica) and Terminalia bellerica (T. bellerica) extracts on human hepatocellular carcinoma (HepG2), and lung carcinoma (A549) cells and their synergistic effect with doxorubicin or cisplatin. Methods: HepG2 and A549 cells were treated with P. emblica and T. bellerica extracts either alone or in combination with doxorubicin or cisplatin and effects on cell growth were determined using the sulforhodamine B (SRB) assay. The isobologram and combination index (CI) method of Chou-Talalay were used to evaluate interactions between plant extracts and drugs. Results: P. emblica and T. bellerica extracts demonstrated growth inhibitory activity, with a certain degree of selectivity against the two cancer cell lines tested. Synergistic effects (CI < 1) for P. emblica/doxorubicin or cisplatin at different dose levels were demonstrated in A549 and HepG2 cells. The T. bellerica/cisplatin or doxorubicin also showed synergistic effects in A549 and HepG2 cells. In some instances, the combinations resulted in antagonistic effects. The dose reduction level was different and specific to each combination and cell line. Conclusion: The growth inhibitory activity of doxorubicin or cisplatin, as a single agent, may be modified by combinations of P. emblica or T. bellerica extracts and be synergistically enhanced in some cases. Depending on the combination ratio, the doses for each drug for a given degree of effect in the combination may be reduced. The mechanisms involved in this interaction between chemotherapeutic drugs and plant extracts remain unclear and should be further evaluated. © 2008 WJG. All rights reserved.